Implementasi Ketrampilan Abad 21 Berorientasi Kurikulum Merdeka pada Pembelajaran Projek Penguatan Profil Pelajar Pancasila - Yulia Ima Riswati; Tutut Suryaningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the implementation of 21st-century skills oriented toward the Merdeka Curriculum through the Pancasila Student Profile Strengthening Project (P5) at SMAN 1 Rejotangan. A qualitative research approach was employed, with data collected through observation, interviews, documentation, and triangulation. The research subjects included Grade X students, homeroom teachers, and the vice principal of curriculum affairs. The findings reveal that the implementation of 21st-century skills—critical thinking, creativity, collaboration, communication, and digital literacy—has been effectively integrated into the P5 project under the theme Sustainable Lifestyle. The project activities fostered students’ environmental awareness, independence, creativity, and social responsibility. The planning, implementation, and evaluation stages were conducted systematically, with teachers serving as facilitators and students as active participants. Optimization efforts were carried out through teacher capacity building, technology integration, and collaboration with external partners. The study concludes that implementing the Merdeka Curriculum through P5 effectively cultivates adaptive, innovative, and character-driven learners based on the values of Pancasila